Peningkatan Mutu Lulusan Melalui Jaringan Kemitraan Dengan Dunia Usaha Dan Dunia Industri di SMK PGRI 2 Ponorogo - Fata Asyrofi Yahya; Maydatullaela (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
Vocational education in Indonesia is implemented through Vocational High Schools (SMK). SMKs are expected to be able to create graduates who are ready to work. However, in reality, the absorption of SMK graduates is still low. One way to overcome this is by building partnerships with DUDI. Building partnerships is very important to improve the quality of graduates of these educational institutions. Based on this, this study aims to examine the concept of partnership between schools and the business world and the industrial world in improving the quality of graduates. The research model used in this research is a qualitative method with data collection techniques through interviews, observation, and documentation. From the data analysis, it can be concluded that SMK PGRI 2 Ponorogo has carried out several stages in building partnerships. In addition, they also use a network model in the form of industrial classes and a collaboration model in the form of recruitment of students, internships, and PKL. As for the success in this partnership in the form of increasing academic aspects in the form of increasing the competence of students and winning championships in several competitions. While in the non-academic aspect in the form of increased curiosity of students, and the social aspects of students in the form of high compassion for others and high solidarity.